INTRODUCTION OF PRINCIPLES OF UNIVERSAL DESIGN IN ORGANIZATION OF HOUSING SPACE OF PEOPLE WITH DISABILITY (Physical Culture and Sport: Scientific Perspective, 2023)
In the article the question of necessity of introduction of principles of universal design is examined in organization of housing space of persons with disability. Convention of the UN about rights for people with disability determines the necessity of providing to the persons with disability of availability of physical, social, economic and cultural surroundings, health protection and education, and also to information and connection that can assist creation for them possibilities to a full degree to use all human rights and fundamental freedoms. The state must create for people with disability possibility to conduct the independent and valuable way of life, id est to accept certain measures for the removal of any obstacles, that bother or do impossible access to building, transport, and also to other objects and services (schools, dwelling-houses, medical establishments, pharmacies, shops and workplaces) for people with disability.The people with disability need specific care, and they need a special architectural and spatial environment to lead a normal life. This is especially relevant for disabled people with musculoskeletal disorders functions, because when designing any environment for them, next to the specifics lifestyle, it is necessary to take into account the dimensions of wheelchairs and other devices used by disabled people for movement.It is possible to work out simple methods many problems not only in the again built-up districts of cities but also at a reconstruction or modernization of housing building and her separate objects. Ideas are worked out on the basis of front-rank foreign and home standards, suggestions and wishes of many people with disability. First of all it behaves to the ramp at entrances to building and transitions through the traffic way of streets. Ramp it is recommended to set, as a rule in addition to a stair and to accompany them. In those cases, when it maybe, folding or removable ramp used as frames from strong materials with directing channels for wheels.
Keywords: universal design; man with disability; availability; wheels; quality of life; integration; society